ENTREPRENEURSHIP-INSIGHTED VILLAGE-OWNED ENTERPRISE (BUMDes) LEADERSHIP CONCEPT IN REALIZING A COMPETITIVE AND SUSTAINABLE DEVELOPMENT STRATEGY OF THE SINARANCANG TOURISM VILLAGE - Muhfidlatul Qira'ati (Journal of Green Science and Technology, 2021)
Sinarancang Village as the Setu Patok area has the potential for natural tourism and potential open public spaces. Sinarancang Village has a strategic location because it is close to Setu Patok. The potential for natural and river tourism along with the community mortar home industry are some of the attractions that motivate BUMDes Rancang Jaya to develop it as a tourist village. BUMDes Rancang Jaya, as a newly established company owned by the Village of Sinarancang, has a vision of creating a tourism village called Sinarancang, which is able to attract Cirebon tourists to visit. BUMDes Rancang jaya has been observing and studying other BUMDes that have succeeded in developing tourist villages and attracting tourists. They see the motivation of tourists in visiting Sinarancang Village because of its location near Setu Patok with beautiful views. This is one of the reasons why tourism needs to be developed for developing villages as a means of capturing new opportunities in meeting community needs. The purpose of this study is to identify entrepreneurial characteristics that are applied in business development carried out by BUMDes and to describe the concept of BUMDes leadership which has entrepreneurial characteristics in realizing the development strategy of the Sinarancang tourism village. This study used a qualitative descriptive method with secondary data analysis in the form of village policy documents and primary data analysis from observations and interviews. Regional leadership needs to demonstrate entrepreneurial characteristics. In this case, the leadership of BUMDes Rancang Jaya has shown the beginnings of entrepreneurial characteristics according to Schumpeter (1934) and Kirzner (1973), namely believing in change and making innovations in institutional settings. To realize the development strategy of the Sinarancang Tourism Village, it requires BUMDes leadership with entrepreneurial insight, namely those that fulfill 6 entrepreneurial characteristics in the context of regional development (Stimson, 2009), so that the motivation of entrepreneurship in the context of regional development is realized, namely creating individual economic benefits that occur from cultural enhancement or the regional economic context (business climate) and social welfare as well as community benefits stemming from spillover and institutional effects.Keywords: Sinarancang, Tourism Village, BUMDes, Regional Leadership, Entrepreneurship